2018
DOI: 10.21206/bjsa.v7i4.431
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Produtividade De Grãos E De Biomassa Em Dois Híbridos De Milho Submetidos À Duas Condições De Adubação No Município De Santarém - Pa

Abstract: Com o desenvolvimento da exploração avícola na cidade de Santarém/PA, o uso da cama de aviário como fertilizante é uma opção atrativa para a exploração de culturas como soja e milho, bem como hortaliças. O objetivo deste trabalho foi estudar a produtividade de grãos e de biomassa de dois híbridos de milho submetidos a duas condições de adubação no município de Santarém/PA. Foi avaliada a combinação entre dois fatores, cultivares e adubação. As cultivares híbridas de milho foram: Híbrido CD384Hx Coodetec® e Híb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Such increases can be attributed to better vegetative development (height and diameter of the plant). However, lower GRN can result in ears with smaller diameters, which can be detrimental to the hybrid's yield potential (Guerra et al, 2017). Revista de Agricultura Neotropical, Cassilândia-MS, v. 9, n. 4, e6849, oct./dez.…”
Section: Resultsmentioning
confidence: 99%
“…Such increases can be attributed to better vegetative development (height and diameter of the plant). However, lower GRN can result in ears with smaller diameters, which can be detrimental to the hybrid's yield potential (Guerra et al, 2017). Revista de Agricultura Neotropical, Cassilândia-MS, v. 9, n. 4, e6849, oct./dez.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the benefits promoted by P. chlamydosporia, the addition of poultry litter to the soil increases the availability of nutrients such as nitrogen, phosphorus and potassium for the cultivation of corn. Guerra et al (2017) when developing a study with organic fertilization in the corn crop, found that plants that received 2 t ha -1 of poultry litter, expressed higher yield in relation to those that were not treated with organic compost. In this way, it is believed that the short period of time between the application of the soil poultry litter without mechanical incorporation and the sowing of soybeans, may have caused injuries to the roots due to the decomposition process of the organic material, causing a decline in productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Analisando as doses de cama de frango, verifica-se que apenas a dose 0 teve índice de matéria seca igual ou menor que 30%, assim, a partir da dosagem de 5 t ha -1 , as cultivares obtiveram produtividade de matéria seca maior que 40% (Figura 8D). Guerra et al (2017) evidenciaram os benefícios do emprego de adubos orgânicos na melhoria da qualidade do solo e, consequentemente, no desenvolvimento e produtividade da cultura.…”
Section: Corroborando Com As Informações Apresentadas Peixotounclassified